Synthesis of Fully Deacetylated Quaternized Chitosan with Enhanced Antimicrobial Activity and Low Cytotoxicity - Yeon Ho Kim; Ki Sun Yoon; Sung-Jae Lee; Eun-Jung Park; Jong-Whan Rhim (MDPI AG, 2022)
Fully deacetylated quaternary chitosan (DQCTS) was prepared by replacing the carboxyl group of chitosan with a quaternary ammonium salt. The DQCTS was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and nuclear magnetic resonance (NMR). The antimicrobial activity of DQCTS was evaluated using the minimum inhibitory concentrations (MIC) methods and time-kill assay. DQCTS exhibited strong antibacterial and antifungal activity against Staphylococcus aureus, Escherichia coli O157: H7, Candida albicans, and Aspergillus flavus. Especially, the antifungal activity against C. albicans of DQCTS was greatly improved at 15.6 µg/mL of MIC and 31.3 µg/mL of minimum fungicidal concentration (MFC). Expression levels of virulence genes of microorganisms were also significantly decreased by DQCTS treatment, and the risk of virulence of microorganisms might be decreased. The result of the cytotoxic effect of DQCTS on human skin cells (HaCaT cells) indicated that the cytotoxicity of DQCTS on HaCaT cells was nearly non-toxic at 50 μg/mL. The DQCTS, with strong antimicrobial and low toxicity, has a high potential for use in functional food packaging and biomedical applications.